2020
DOI: 10.1016/j.eml.2020.100786
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-open ventilated metamaterial absorbers for sound-silencing applications in environment with free air flows

Abstract: For most acoustic metamaterials, once they have been fabricated, their operating frequencies and functions cannot be adjusted, which is an intrinsic barrier for development of realistic applications. The study to overcome this limit has become an urgent issue at the heart of acoustic metamaterial engineering. Although with the advance of metamaterials in the past two decades, a series of methods such as electric or magnetic control have been proposed, most of them can only work in the condition of no fluid pas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…We note that the thickness of the bilayer metasurface is in a subwavelength scale (1/5th) compared to the lower limit (305 Hz) of the absorption band. In addition, the relative bandwidth of absorption here is much larger than (7 times of) recent results with using a pair of Helmholtz resonators in the unit cell [37]. If the same wide absorption band is desired, seven pairs of Helmholtz resonators need to be adopted in the unit cell [37].…”
Section: Structuresmentioning
confidence: 79%
See 2 more Smart Citations
“…We note that the thickness of the bilayer metasurface is in a subwavelength scale (1/5th) compared to the lower limit (305 Hz) of the absorption band. In addition, the relative bandwidth of absorption here is much larger than (7 times of) recent results with using a pair of Helmholtz resonators in the unit cell [37]. If the same wide absorption band is desired, seven pairs of Helmholtz resonators need to be adopted in the unit cell [37].…”
Section: Structuresmentioning
confidence: 79%
“…If the same wide absorption band is desired, seven pairs of Helmholtz resonators need to be adopted in the unit cell [37]. Moreover, when more different resonators are adopted in the unit cell, their coupling effects become more complex, resulting in lower peak absorption (< 92%) observed in experiments [37]. waves.…”
Section: Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The acoustic performance of the presented acoustic metastructures can be customized as per the requirements. More recently, Xiang et al [109] demonstrated an ultra-open ventilated metamaterial absorber (UVMA). The absorber was comprised of weakly coupled split-tube resonators, which resulted in a simultaneous high-efficiency absorption and ventilation.…”
Section: Acoustic Meta-absorbersmentioning
confidence: 99%
“…Near-perfect sound absorption can be achieved in metasurfaces with a small open area ratio 32 36 . However, high absorption is still hard to achieve especially when the metasurfaces have a large open area ratio 37 , 38 . In addition, the bandwidths of absorption peaks are usually narrow and difficult to adjust.…”
mentioning
confidence: 99%